PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SMA - Mardhani, Slamet Dini Tiara; Haryanto, Zeni; Hakim, Abdul (EduFisika: Jurnal Pendidikan Fisika, 2022)
This study aims to determine the improvement of students' critical thinking skills at SMA Negeri 6 Berau through the application of a problem-based learning model to dynamic fluid material. This type of research uses a quantitative approach with the pre-experimental design method in the form of one-group pretest-posttest. The population in this study were students of class XI MIPA SMA Negeri 6 Berau totaling 3 classes with a sample of 31 students in class XI MIPA 1. Data collection used a test technique of 10 essay questions given before and after treatment. The results showed that there was an increase in students' thinking skills after applying the problem based learning model. This can be proven based on data analysis which obtained an average pretest of 20.45 and an average posttest of 76.74. Based on the results of the paired t test analysis, it was found that there were significant differences in the results of the pretest and posttest.